Biogeographic Regionalization of South American Anurans - Vasconcelos, Tiago S. [UNESP]; Silva, Fernando R. da; Santos, Tiago G. dos; Prado, Vitor H. M.; Provete, Diogo B.; Vasconcelos, TS; DaSilva, FR; DosSantos, TG; Prado, VHM; Provete, DB (Springer, 2019)
The interest in recognizing spatial patterns of species co-distributions has long led biogeographers and macroecologists to classify the world in biogeographic regions. In this chapter, we aimed to identify regions with distinct species pools, thus representing different biogeographic regions with co-occurring species of anurans in South America. Using quantitative and clustering methods, we recognized six anuran biogeographic regions in South America: two regions are predominantly tropical (named as AMAZON and DIAGONAL-AF); two regions are associated to the Andes mountains (named as MID-ANDES and NORTH-/SOUTH-ANDES); and two regions are broadly located south of the Tropic of Capricorn (named as SUB-TROPICAL and TEMP-GRASS). Using regression and variation partitioning analyses, the six distinct biogeographic regions are mainly predicted by differences in climatic gradients among the biogeographic regions (e.g., clusters located in the different tropical, subtropical, and temperate regions). Yet, the combination of rough topography and habitat structure of major biomes was also a good predictor for other biogeographic regions (e.g., the recognition of the different Andean biogeographic regions having different major biomes, such as montane forests and grasslands).
Keywords: Anura; Biogeographic regions; Bioregionalization; Climate hypothesis; recluster.region; South America